Self-directed learning readiness among II and III MBBS students in a tertiary teaching hospital - Prabhakar, Ram; Masilamani, Thiruvenkadam; Ananthan, Velmurugan Anbu (International Journal Of Community Medicine And Public Health, 2020)
Background: Self-directed learning (SDL) is defined as an instructional stratagem where the medical students, with guidance from the teacher, choose what and how they will learn. The current study is aimed at finding the readiness for SDL among medical students and its association with their socio demographic characteristics. Methods: An Institution based cross-sectional study was conducted among 100 II Bachelor of medicine and Bachelor of Surgery (MBBS) students and 100 III MBBS students of Theni Government Medical College. The readiness assessment of the students was found by using Fischer’s 40 items SDL readiness score (SDLRS) instruments. The instrument has 40 items under three domains self-management (9 items), desire for learning (16 items) and self-control (15 items). Results: Only 29% were aware of SDL. Around 55% showed high readiness for SDL (>150). Females had higher readiness for self-directed learning than males (60.9% versus 39.1%) but the mean SDLR score was similar 152.5 versus 151.6. III MBBS medical students had higher score than II MBBS medical students (58.2% versus 48.8%, mean SDLR score 149.9 versus 154.2, p=0.011). Demonstrating higher readiness for SDL was not associated with area of residence, stay, presence of doctor in the family, type of schooling, medium of school education, age and gender. Conclusions: There is need of hour to address medical students’ SDL skills to update their competencies. SDL readiness scales help medical faculty to assess students’ learning capabilities and improve teaching learning strategies.